Evaluation of serum presepsin concentrations as a biomarker of sepsis in high-risk neonates - Hosny M.A El-Masry; Alaa-Eldin A Hassan; Hesham H Amin; Mohamed A Abd Elmoaty (Wolters Kluwer Medknow Publications, 2021)
Background Sepsis is a common cause of morbidity and mortality among neonates. The clinical usefulness of assessment of presepsin concentration was studied and compared with other laboratory parameters in a prospective case-control study. Patients and methods A prospective case-control study was carried out in the neonatal intensive care unit of Al-Azhar University Hospital (Assiut, Egypt) from July 2016 to July 2018. The authors enrolled 80 newborns: 40 at high risk of neonatal sepsis (group A), 20 septic (group B) according to Tollner clinical sepsis score greater than 2 and/or positive blood culture, and 20 controls (group C). Full medical history, clinical examination, estimation of gestational age by new Ballard score, and laboratory investigations were done. Presepsin, C-reactive protein (CRP), complete blood count, and blood culture were done during first day (D1) of admission for all neonates. Additional measurements of presepsin and CRP were done at D3 for group A, and another measurement at D5 for neonates who have increased CRP and/or appearance of signs of sepsis (group A) at D3. Result Initial levels of serum presepsin in 80 neonates ranged from 293 to 1648 pg/ml. Presepsin had a significant difference between groups A and B (692.9±79.49 and 1327.3±208.41 pg/ml, respectively; P<0.001FNx18). In group A, neonates who developed clinical signs of sepsis, presepsin levels had significant difference between D1, D3, and D5 (P<0.001FNx18). Presepsin had a significant difference between full-term and preterm neonates (P<0.001FNx18). There was a positive correlation of presepsin with CRP and white blood cells (r=0.580 and 0.546, respectively). Coagulase-negative staphylococci were the most isolated organism. The receiver operating characteristic curve of presepsin at enrollment shows an area under the curve of 0.99. The best calculated cutoff value was greater than or equal to 722 pg/ml, with 100% sensitivity and 97.5% specificity. Conclusion Presepsin level changes early in the disease course, so it can be used as a reliable biomarker for early diagnosis of neonatal sepsis, and it is a promising marker for detection of improvement.